Pengaruh Company Size, Company Ages, Profitability, dan Leverage terhadap CSR Disclosures pada Kelompok Perusahaan Properti dan Real Estate yang Terdaftar di BEI - Sunaryo, Sunaryo (Journal the Winners: Economics, Business, Management, and Information System Journal, 2013)
The primary objective of this research is to learn the effect of company size, company ages, profitability, and leverage variables on corporate social responsibility disclosures variable, either simultaneously or partially. Secondary data were collected by purposive sampling of property and real estate company groups listed in IDX and the preceding scientific journals. Research used simple regression to test the hypothetical simultaneously. The results of this research describe that company size, company ages, and leverage variables do not have significant effect on the corporate social responsibility disclosures variable; only profitability variable has significant effect on the corporate social responsibility disclosures variable. It is recommended that the topic of this research can be continued with agribusiness and mining company groups, or adding new independence variables.